PENGARUH KARAKTERISTIK DEWAN KOMISARIS, KOMITE AUDIT , DAN KESULITAN KEUANGAN TERHADAP FEE AUDIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2014 - Fadel Iswandi Prawira; Yuneita Anisma; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to identify and analyze the influence of board characteristics (board size, board independence, and board meet), audit committee ( audit committee size, audit committee independence, audit committee experts, and audit committee meet), and financial distress to audit fee. This research used secondary data from annual reports and financial reports of manufacturing industry which listed in Indonesian Stock Exchange (IDX) during 2010-2014 periods This study uses purposive sampling method and uses multiple linear regression as the analysis instrument, by Using SPSS (Statistical Product and Service Solution) ver. 17 software. The first and the fourth hypothesis shows that partially there are significant influences between the size of the board commissioner and the size of the audit committee on the audit fee. While the independent commissioner, the meeting intensity of the board commissioner, the independence of the audit committee, the size of the audit committee member’s expertise, the meeting intensity of the audit committee, and financial distress don’t influence significantly the audit fee. The influence of the characteristics of the board commissioner, audit committee and financial distress are 45,3%, while the remaining 54,7% is influenced by other variables.Keywords : board of commissioner , audit committe, and financial distresss.